2011
DOI: 10.1901/jeab.2011.96-123
|View full text |Cite
|
Sign up to set email alerts
|

Behavior‐based Assessment of the Auditory Abilities of Brushtail Possums

Abstract: Brushtail possums (Trichosurus vulpecula) were trained to press a right lever when a tone was presented (a tone-on trial) and a left lever when a tone was not presented (a tone-off trial) to gain access to food. During training the tone was set at 80 dB(A), with a frequency of 0.88 kH for 3 possums and of 4 kH for the other 2. Once accuracy was over 90% correct across five consecutive sessions, a test session was conducted where the intensity of the tone was reduced by 8 dB(A) over blocks of 20 trials until ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Overall accuracy on novel S+ trials was 90.3%, and each of the five rats showed accuracies that were significantly above chance (binomial p < .05 in each case). These data are thus consistent with previous research in our laboratory showing that rats can learn generalized non-match or oddity concepts with olfactory stimuli (April, Bruce, & Galizio, 2011). …”
Section: Resultssupporting
confidence: 92%
“…Overall accuracy on novel S+ trials was 90.3%, and each of the five rats showed accuracies that were significantly above chance (binomial p < .05 in each case). These data are thus consistent with previous research in our laboratory showing that rats can learn generalized non-match or oddity concepts with olfactory stimuli (April, Bruce, & Galizio, 2011). …”
Section: Resultssupporting
confidence: 92%
“…The exceptional olfactory discrimination abilities of rodents have led to their use in applied settings to detect explosives and diagnose tuberculosis (Poling et al, 2011). Rats can also learn conditional discriminations fairly rapidly with odor stimuli (Lu, Slotnick, & Silberberg, 1993) and generalized identity and oddity have been demonstrated as well (April, Bruce, & Galizio, 2011; Pena, Pitts, & Galizio, 2006; Prichard, Panoz-Brown, Bruce, & Galizio, 2015). …”
Section: Delayed Matching-to-sample (Dmts) and Non-matching To Samplementioning
confidence: 95%
“…The common brushtail possum (Trichosurus vulpecula), a phalangerid that occurs in Tasmania, had more sensitive brainstem responses than the quoll's overall, and was most sensitive at a higher frequency, 17-19 kHz (Gates and Aitkin 1982). Behavioural assays of possums showed that hearing sensitivity increased from 2 to 15 kHz, and was sustained from 20 to 35 kHz (Osugi et al 2011).…”
Section: Effectiveness Of Acoustic Stimulimentioning
confidence: 99%